Association between dust from gold mine dumps respiratory symptoms and diseases among adolescents and the elderly in Gauteng and North West Provinces South Africa - Voyi, Kuku V.V. (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.